Transplantation at Rizk Hospital - Zeineh, S. (1998)
From April 1985 until November 1997, a total of 228 kidney transplants were performed at our center. Our activity was slow in the first 5 years, owing to the civil war in Lebanon. In 1990 we were able to planify our program and start transplanting from local cadaveric donors (CAD).